جمالية المكان في قصيدة "المغيرية" لـــ "سعد مردف" - جيهان بوذراع; ذكرى بن عمار; يسرى ترعة; يمينة بوعود (University of Eloued جامعة الوادي, 2025)
الملخص: أن المكان في ليس مجرد منطقة ذات خصائص مادية وبشرية بحتة ومترابطة بل أكثر من ذلك، فهو عنصر جمالي ودلالي يلعب دوراً فاعلاً في بنية الواقع بالصورة والذات معاً. وكما تطرقنا إلى المكان والمصطلحات المجاورة كالفضاء والحيّز والإنشاء، والموضع التي تثير دهشتنا وذلك بإستنطاقنا لتفسيحات المكان التي تتضمن أماكن مفتوحة ومغلقة وأليفة ومعادية، وما يحدده الشاعر من المكان المفتوح الذي يكون منفتحاً على العالم، والمكان المغلق الذي يكون منغلقاً على العالم، والمكان الأليف الذي يألفه الإنسان والمعادي الذي لا يوجد فيه راحته. وكذلك أيضاً تطرقنا إلى المكان بوصفه موضوعاً للإبداع الشعري الذي يتضمن وصف المكان، والحنين إليه، وكذلك دلالة المكان، تتضمن زيارة المدن والمعالم؛ وأيضاً تطرقنا إلى الإنسان والمكان والعلاقة بينهما، فهي علاقة مؤثرة وحميمية وتتداخل فيها أبعاد اجتماعية ونفسية، فالمكان لا يعد مجرد إطار جغرافي يعيش فيه الإنسان بل هو جزء من هويته وذاكرته وتاريخه. رؤى المكان الجمالية تتجلى في عدة صور في حياة الشاعر سعدي يوسف (الجزائر الذي ولد في بلدة "اسطيل" بالوادي). خلصت طرحنا أيضاً إلى أبعاد المكان التي تتضمن البعد (الديني، والنفسي، والاجتماعي، والتاريخي)؛ وأيضاً خلصت طرحنا إلى المكان والرموز الأسطورية وروحانية الأشياء والإشارة. Résumé :فرنسية أو انجلزية Place is not merely an area with purely physical and human characteristics that are interconnected. Rather, it is an aesthetic and semantic element that plays an active role in the structure of reality, both in image and in subject. We also touched upon place and related terms such as space, area, construction, and location, which amazed us by examining the expanses of space, which include open and closed, familiar and hostile places. We also explored what the poet defines as an open place that is open to the world, a closed place that is closed off from the world, a familiar place that is familiar to humans, and a hostile place that is uncomfortably unsettling. We also touched upon place as a subject of poetic creativity, which includes descriptions of place and longing for it. We also touched upon the significance of place, including visits to cities and landmarks. We also touched upon people and place and the relationship between them, which is an influential and intimate relationship, intertwined with social and psychological dimensions. Place is not merely a geographical framework in which humans live, but rather a part of their identity, memory, and history. Aesthetic visions of place are manifested in several forms in the life of the poet Saadi Youssef (born in Algeria in the town of Astil in El Oued). Our thesis also addresses the dimensions of place, including religious, psychological, social, and historical dimensions. It also addresses place, mythological symbols, and the spirituality of objects and signs.
مذكرة ليسانس. دراسات ادبية.2025
Keywords: المكان، جماليات المكان، المكان موضوعا للإبداع الشعري